Proxy-guided Image-based Rendering for Mobile Devices - Reinert, Bernhard; Kopf, Johannes; Ritschel, Tobias; Cuervo, Eduardo; Chu, David; Seidel, Hans-Peter (Pacific Graphics 2016, 2016)
VR headsets and hand-held devices are not powerful enough to render complex scenes in real-time. A server can take on the rendering task, but network latency prohibits a good user experience. We present a new image-based rendering (IBR) architecture for masking the latency. It runs in real-time even on very weak mobile devices, supports modern game engine graphics, and maintains high visual quality even for large view displacements. We propose a novel server-side dual-view representation that leverages an optimally-placed extra view and depth peeling to provide the client with coverage for ﬁlling disocclusion holes. This representation is directly rendered in a novel wide-angle projection with favorable directional parameterization. A new client-side IBR algorithm uses a pre-transmitted level-of-detail proxy with an encaging simpliﬁcation and depth-carving to maintain highly complex geometric detail. We demonstrate our approach with typical VR / mobile gaming applications running on mobile hardware. Our technique compares favorably to competing approaches according to perceptual and numerical comparisons. This project was done in collaboration with Max Planck Institute. For additional materials and presentations slides please visit the project site at MPI